Image as embodiment of cultural knowledge - Borjan, Etami (2011)
Postcolonial ethnographic film production has obliterated the Cliffordian “savage paradigm” model of representation and has given space to different histories and voices. New voices have undermined authority and dominance of the Western discourse, which can be understood as a part of a larger process that George Marcus and Michael Fischer call “crisis of representation”. The voice of Western filmmaker has become one among many and it has lost its absolute authority. The Other is no longer a studied object, but an active participant in the production of filmic text. The process of looking at the Other is not easily rationalized. The separation between “us” and “them” is deeply rooted inside both anthropology and ethnographic film. Embodied knowledge of the Other disperses binary and realistic knowledge. Ethnographic film has become a field for production of political and social realities. Thus image is not perceived as a pure representation but as a political act and a tool for controlling one’s cultural identity. Collaborative film, indigenous media, auto-ethnography are just some of the examples of new forms of shared authorship between the filmmaker and the studied subjects. Images enact symbolic forms of power. Therefore representing the Other raises the question of responsibility and legitimacy ; of power and authorship. Images create concepts as well as embody cultural concepts. Jay Ruby (1995) claims that an anthropologist can’t escape moral responsibility towards the culture that s/he represents no matter what method s/he is using. His claim raises important questions of power and meaning that images have in different cultures. It also questions the values that images have in Western cultures as opposed to non-Western worlds. Do images necessarily victimize the Other? Can images convey gestural language? Do images embody cultural knowledge as Sol Worth and John Adair claimed?
Projekt MZOS
ENG